Combustion of jojoba-oil/diesel blends in a small scale furnace. (February 2019) - Al Omari, Salah A.B.; Hamdan, Mohammad O.; Selim, Mohamed YE.; Elnajjar, Emad
Abstract: This experimental study investigates the combustion and pollutants emissions from a small scale furnace burning diesel fuel blended with raw jojoba oil. Jojoba oil to diesel proportions in the blends (on mass basis) ranging from 0 to 35% are considered for total blended fuel flow rate of about 8 kg/h. Higher fuel supply rates of about 10 kg/h were needed in order to allow for reaching higher jojoba share in the blends up to about 60%. This allows for securing sufficient amount of the higher volatility component (diesel) whose combustion would support the vaporization and subsequent ignition and combustion of the heavier jojoba oil. The presence of jojoba in the blends leads to a clear reduction in NOx and hydrocarbon (HC) emissions but it showed less impact on CO levels. Due to its high viscosity, jojoba in the blends impacts spray formation hence seems to have an indirect detrimental effect on CO emissions. Moreover, jojoba oil in the blends adversely impact thermal radiation to furnace walls due to less sooting tendency of the flame when jojoba is present. To some extent, this is also attributed to the way jojoba influences spray processes. Highlights: Raw jojoba-oil/diesel blends are used as fuel for small furnace. 0–35% by weight of jojoba in blends is used with input fuel supply of 8.3 kg/h. Stable flame was possible with 60% jojoba share if fuel input is 10 kg/or higher. Jojoba reduces NOx and hydrocarbon emissions but indirectly impacts CO emissions. Jojoba oil in the blends has adverse impact on thermal radiation to furnace walls.